A study of heart rate variability in diabetic mellitus patients - Srinivasa Jayachandra; Satyanath Reddy Kodidala (Mìžnarodnij Endokrinologìčnij Žurnal, 2022)
Background. Heart rate variability (HRV) is reduced in diabetes mellitus (DM) patients, suggesting dysfunction of cardiac autonomic regulation and an increased risk for cardiac events. Cardiac autonomic neuropathy (CAN), which results from damage to autonomic nerve fibers that innervate the heart and blood vessels, is a serious complication of DM. During progression of CAN, the parasympathetic nerve fibers innervating the heart are affected before the sympathetic nerve fibers leading to a reduced heart rate variability. The purpose of this study was to examine type 2 diabetes patients with heart rate variability in order to diagnose autonomic dysfunction and to relate the findings to other complications of diabetes mellitus. Materials and methods. 41 type 2 M patients and 45 age- and sex-matched controls were included. In the time domain we measured the mean R–R interval (NN), the standard deviation of the R–R interval index (SDNN), the standard deviation of the 5-min R–R interval mean (SDANN), the root mean square of successive R–R interval differences (RMSSD) and the percentage of beats with a consecutive R–R interval difference > 50 ms (pNN50). In the frequency domain we measured high-frequency power (HF), low-frequency power (LF) and the LF/HF ratio. Results. There was no statistically significant difference between DM patients and controls for age and sex distribution. All time- and frequency-domain parameters except mean R–R interval and the LF/HF ratio were significantly lower in diabetes patients than in controls. When chronic complications of DM were examined, diabetic retinopathy and nephropathy were usually present together. For example, among six patients with nephropathy five also had retinopathy. There were 13 diabetes patients with complications (diabetic nephropathy and/or retinopathy) and nine patients with no diabetic complications. Although the chronological ages of the diabetes patients with and without complications were similar (53 ± 9 and 49 ± 12 years, respectively; P > 0.05), the duration of DM in patients with complications was significantly greater than that of those without complications (14 ± 9 versus 5 ± 7 years; P = 0.002). Diabetes patients had lower HRV values for time-domain and frequency-domain parameters than controls. Conclusions. Majority of heart rate variability parameters were lower in diabetes patients with chronic complications than in those without complications.